Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/antibiotics11030333
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Patterns of Drugs Given to Hospitalized COVID-19 Patients: A Cross-Sectional Study in Colombia

Abstract: The impact of COVID-19 prompted a race to find a treatment that would reduce its mortality. Most studies have not shown favorable results for many of these drugs, but they are still used. The aim as to determine the differences and similarities in the hospital pharmacological management of patients with COVID-19 according to sex, age group, and geographical region of Colombia, 2020–2021. Descriptive cross-sectional study was conducted on the prescription patterns of the medications given to patients diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Overall, guideline-adherent care was high for both centers. Adherence to dexamethasone use in this study was similar to prescription patterns reported in other COVID-19 centers globally (70 to 95%), [9][10][11][12] with the high utilization rate being influenced significantly by the result of the RECOVERY trial. 9 Underuse of tocilizumab appears to be related to supply issues during the study period.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, guideline-adherent care was high for both centers. Adherence to dexamethasone use in this study was similar to prescription patterns reported in other COVID-19 centers globally (70 to 95%), [9][10][11][12] with the high utilization rate being influenced significantly by the result of the RECOVERY trial. 9 Underuse of tocilizumab appears to be related to supply issues during the study period.…”
Section: Discussionsupporting
confidence: 83%
“…13 Despite the aforementioned shortage, the adherence to tocilizumab seen in this study is higher than the prescription patterns reported in other COVID-19 centers across the world (0.5 to 40%). 9,[14][15][16] Overuse of empiric antibiotics is associated with disease severity (i.e., more severe cases are given antibiotics without sufficient indication) and location of treatment (i.e., ICU patients are given antibiotics without sufficient indication). A similar trend was observed in the use of azithromycin where highest adherence rates were seen in mild cases and the lowest adherence seen in critical cases.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used drug in this study was Corticosteroids (48%) followed by Remdesivir & Tocilizumab. Luis Fernando et al descriptive study showed commonly used drug was corticosteroids (66.3%) 6 . The probable reason for use of corticosteroids was to reduce inflammatory events & to prevent cytokines storm.…”
Section: Discussionmentioning
confidence: 98%
“… 13 Widespread off‐label use of unproven drugs for COVID‐19 was rampant in many other countries across the world. 14 , 15 This may in part be because COVID‐19 arrived later in NZ as well as differences in characteristics of the health systems.…”
Section: Discussionmentioning
confidence: 99%
“…The NZ experience contrasts with countries such as the United States, where new prescriptions for hydroxychloroquine or chloroquine were more than seven times higher in March 2020 compared with the previous year, across both primary and secondary care settings 13 . Widespread off‐label use of unproven drugs for COVID‐19 was rampant in many other countries across the world 14,15 . This may in part be because COVID‐19 arrived later in NZ as well as differences in characteristics of the health systems.…”
Section: Discussionmentioning
confidence: 99%